Self- and N2- broadening of CO in the low-pressure regime. Issue 1 (1st January 2023) - Tan, Y.; Hua, T.-P.; Tang, J.-D.; Wang, J.; Liu, A.-W.; Sun, Y. R.; Cheng, C.-F.; Hu, S.-M.
Abstract: Sub-Doppler saturated absorption spectroscopy of rovibrational transitions of carbon monoxide broadened by nitrogen was recorded at low pressures (1-24 Pa) near 1.56 µ m with comb-locked cavity ring-down saturation spectroscopy. We found a nonlinear pressure dependence of the Lamb-dip width of the CO transition induced by elastic scattering. Analysis of the results allows us to characterize parameters of elastic- and nonelastic- scattering under collisions. The elastic scattering angle for nitrogen-induced collisions (CO-N2 ) was determined to be larger than 0.6 × 10 −3 rad. The line broadening of the Lamb dip in the region of low pressures exceeds the broadening at high pressures by a factor of 4 and 5 for the self- and N2 -broadening CO R(9) transition. Moreover, much smaller line shifts for both self- and N2 -broaden Lamb dips were observed, which was also attributed to the decrease in the number of scattered molecules in the interaction and the increasing attracting forces.